Synthesis and Structure Elucidation of 4-(4-Amino-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-3-yl-methylene)-2-phenyl-1H-imidazol-5(4H)-one - Hooshang Vahedi; Navabeh Nami; Nasrin Nami (E-Journal of Chemistry)
4-(4-Amino-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-3-yl-methylen)-2-phenyl-1(3H)-imidazol-5-one (5) was synthesized in four steps in high yield. Benzimidinium chloride (1) reacted with dimethyl acetylenedicarboxylate to afford 2-phenyl-4-methoxycarbonylmethylen-1(3H)-imidazol-5-one (2) which was converted to 2-phenyl-4-hydrazinecarbonylmethylen-1(3H)-imidazol-5-one (3) using hydrazine hydrate in methanol. Furthermore, the reaction of (3) with carbon disulfide afforded compound (4) which can be used without further purification to achieve compound (5) using hydrazine hydrate.